OPINIONS REGARDING THE TOURISTIC POTENTIAL OF THE DANUBIAN HARBOURS - MATEI, Elena; PÂRGARU, Ion; STĂNCIOIU, Aurelia-Felicia; BOTOȘ, Andreea (Revista de turism - studii și cercetări în turism, 2013)
In the context of European integration, the creation of transnational tourism products represents the brand of an inter-state collaboration, which, based on a common strategy, implies objectives that aim at achieving the global development of a destination, making thus possible an efficient and effective allocation of resources, in order to achieve a sustainable development, both from a touristic point of view and from an economic, social, cultural, technological, etc. one. The route of the Danube could represent one of the most important European destinations, appertaining to more than one country; therefore, in order to develop and sustain its touristic potential, a common strategy is necessary, with an integrated marketing image, associated to a consistent tourism product, inspiring common values, regardless of the territory of the country it is located in. In this direction, a quantitative marketing research, conducted on 992 respondents, aged 18-24, in order to determine the opinions concerning the touristic potential of the Danubian harbours – as a fundamental element, precursory to the market analysis.